The Determinants of Dividend Policy: A Study of Indonesian Stock Exchange Companies in the Consumer Goods Sector - WIDHIASTUTI, Ni Luh Putu; NOVITASARI, Ni Luh Gde; WIDIASTUTI, Ni Putu (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:A dividend policy is a difficult policy to implement because management needs to determine whether the company's profits will be distributed to shareholders as dividends or retained in the form of retained earnings. Thus, management needs to consider the factors that influence dividend policy. This study aims to determine the effect of liquidity, company size, solvency, company growth, and free cash flow on dividend policy.Methodology:The population in this study were 30 consumer goods industry companies listed on the Indonesia Stock Exchange in 2020-2022. The sample obtained in this study amounted to 90 observations determined by the purposive sampling method. The analysis technique used was the multiple linear regression analysis technique.Findings:The results of the study showed that liquidity, company size and solvency did not affect dividend policy. Company growth had a negative effect on dividend policy. Free cash flow had a positive effect on dividend policy. Further research is expected to add other variables that are more related to dividend policy, such as profitability, investment opportunity, managerial ownership, and institutional ownership.Implication:This research can provide practical implications to various parties, such as company management and investors because the results of this study can serve as a guideline for companies to determine optimal dividend policies and for investors to consider when choosing companies with the potential for dividend payments. Meanwhile, the theoretical implications can add to the reference sources that can enhance the theoretical understanding of the factors that can influence dividend policy.